Understanding pet scams: A case study of advance fee and non-delivery fraud using victims’ accounts - Whittaker, Jack M (The Australian and New Zealand journal of criminology, 2020)
Advance fee and non-delivery frauds have become very common with the growing preference for online shopping and the new opportunities this brings for online offenders. This article uses unique access to a volunteer group’s database focused on preventing pet scams to explore this type of crime. Distances, among other factors, make the purchase of pets online common in countries such as the USA, Australia and South Africa. This modality of purchase has been exploited by organized criminals largely based in Cameroon to conduct advance fee and non-delivery frauds. The article uses data from the volunteer group Petscams.com to provide unique insights on the techniques of the offenders with particular reference to the strategies used to maximize victimization by using real accounts of victims of such frauds. It also briefly notes how the COVID-19 crisis has been used to adapt this type of scam. The article’s discussion identifies the need for a more nuanced assessment into the role of victim oriented voluntary organizations.